Psychophysiological responses to emotions of others in young children with autism spectrum disorders: Correlates of social functioning. Issue 9 (6th April 2017) - Zantinge, Gemma; van Rijn, Sophie; Stockmann, Lex; Swaab, Hanna
Abstract : Studying cognitive and affective mechanisms of social behavior could lead to identifying early indicators of derailing social behavior in young children with Autism Spectrum Disorders (ASD). The present study combined sensitive and objective techniques, such as eyetracking and psychophysiology, to provide insight into early neurodevelopmental mechanisms that are more difficult to uncover when relying on behavioral measures. Social attention towards faces and changes in affective arousal were investigated together in 28 young children with ASD (42–75 months) and 45 nonclinical controls (41–81 months). Children were shown a social‐emotional video clip while eyetracking and heart rate were measured. Children with ASD fixated less on key social‐emotional features within the clip as compared to controls, even though both groups attended equally toward the screen. In contrast to the control group, children with ASD did not show an increase or modulation in affective arousal in response to the social‐emotional scenes. Severity of ASD symptoms, specifically social problems, was associated with arousal modulation and social attention within the ASD group. Early ASD symptoms are associated with impairments in fundamental building blocks of social behavior as expressed in a lack in spontaneous social attention and affective arousal. Such sensitive and objective measures of underlying mechanisms might serve as indicators for tailored approaches in treatment and may help in evaluating effectiveness of early interventions aimed at positively influencing social development and related quality of life in individuals with ASD. Autism Res 2017, 10: 1499–1509 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc.